1997
DOI: 10.1103/physrevlett.79.5126
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Curves of Antiferromagnetic Heisenberg Spin-12Ladders

Abstract: Magnetization processes of spin-1 2 Heisenberg ladders are studied using strong-coupling expansions, numerical diagonalization of finite systems and a bosonization approach. We find that the magnetization exhibits plateaux as a function of the applied field at certain rational fractions of the saturation value. Our main focus are ladders with 3 legs where plateaux with magnetization one third of the saturation value are shown to exist.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
247
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(265 citation statements)
references
References 26 publications
18
247
0
Order By: Relevance
“…The chains are weakly coupled by H ′ = J ′ <i,j> S i · S j with 0 < J ′ ≪ J. The phase diagram of H 1D can be obtained from a numerical solution of the Bethe ansatz equations [12,13], and is shown in Fig. 1.…”
Section: Spin-1/heisenberg Chainsmentioning
confidence: 99%
“…The chains are weakly coupled by H ′ = J ′ <i,j> S i · S j with 0 < J ′ ≪ J. The phase diagram of H 1D can be obtained from a numerical solution of the Bethe ansatz equations [12,13], and is shown in Fig. 1.…”
Section: Spin-1/heisenberg Chainsmentioning
confidence: 99%
“…The present paper is motivated by the recent highfield magnetization measurements 15 in the double-chain S = 1 2 compound NH 4 CuCl 3 which have revealed wellpronounced plateaus at M = 1 4 and M = 3 4 in the temperature range T < 1.5 K. At room temperature, the crystal structure of this material coincides with that of KCuCl 3 , and the main feature is presence of the double chains of edge-sharing CuCl 6 of saturation means that due to a certain rather complicated spontaneous symmetry breaking the magnetic elementary cell contains Q = 8 Cu 2+ ions instead of Q = 2 as suggested by the Hamiltonian symmetry; still, then absence of plateau at M = 1 2 which is characteristic for a single chain 9 is puzzling.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In a variety of models, the magnetization per site m z as a function of the applied magnetic field H exhibits plateaus at certain values of m z ; at those plateaus the magnetization in units of the saturation M = m z /S (here S is the spin of a magnetic ion) is "locked" at some rational number (at least, up to now no indications of the possibility to have plateaus at irrational M were found). Oshikawa et al 4 have shown that in purely one-dimensional systems the allowed values of M , at which the plateaus are possible, are given by the following condition…”
Section: Introductionmentioning
confidence: 99%
“…, q − 1. This corresponds to a q−fold degenerate ground state resulting from the breaking of the discrete translation symmetry, in direct analogy with Mott systems 15 or spin systems 18,19 . The corresponding expectation value of j ⊥ (x) is:…”
mentioning
confidence: 99%